QSAR Studies of 6-Amino Uracil Base Analogues: A Thymidine Phosphorylase Inhibitor in Cancer Therapy - Surya Prakash B. N. Gupta; Neeraj Upmanyu; N. S. Hari Narayana Moorthy; S. Bhattacharya (E-Journal of Chemistry)
A novel series of 6-amino uracil base analogue were synthesized. QSAR study was used to relate the selective nonsubstrate inhibitory activity of 6-amino uracil base analogue with various physicochemical descriptors. Stepwise multiple regression analysis was performed to find out the correlation between various physicochemical descriptors and biological activity of the compounds by using Openstat 2 version 6.5.1 and valstat statistical software. Out of the several equations developed, the best equation having the highest significance was selected for further study. The equation is able to explain 60% of total variance and are more than 95% significant as revealed by the F value.